Perbedaan Tingkat Kecemasan Antara Mahasiswa yang Merokok dan Tidak Merokok di Fakultas Sastra dan Seni Rupa Universitas Sebelas Maret - Naili Nur Sa'adah Nuhriawangsa; . Machmuroch; Diffah Hanim (Nexus Kedokteran Klinik, 2014)
Background: Anxiety disorder have been reported to be associate with increased rates of smoking, increased consumption of cigarettes per smoker, and lower rates of smoking cessation than non-anxiety disordered control groups. In addition, increased anxiety symptoms appear to be correlated with increased rates of smoking. This study aimed to analyze the differences of anxiety level between smoking student and non-smoking student of Faculty Letter and Fine Arts Sebelas Maret University. Method: This study was an observational analytic study with cross sectional approach. The study sample totaled 100 students, between 50 smoking students and 50 non-smoking students of Faculty Letter and Fine Arts Sebelas Maret University class of 2008-2013 which were randomly drawn by purposive sampling technique and continued with simple random sampling. Each respondent was given one standard questionnaire of TMAS (Taylor Manifest Anxiety Scale), L-MMPI (Lie-scale Minnesota Multiphasic Personality Inventory), and standard questionnaire of smokers. The TMAS questionnaire consisting of 50 yes or no option questions, L-MMPI questionnaire consisting of 10 yes or no option questions, and smokers questionnaire consisting of 3 multiple choice questions. The research data were tested with the Chi Square test, and would be continued with the Regression Linier test (?=0,1). Result: There were 13 smoker students had not have anxiety disorder, 10 smoker students had low anxiety disorder, 25 smoker students had moderate anxiety disorder, and 2 smoker students had high anxiety disorder. While 31 non-smoker students had not have anxiety disorder, 10 non-smoker students had low anxiety disorder, 9 non-smoker students who had moderate anxiety disorder, there were not found non-smoker student had high anxiety disorder. From the Chi Square test resulted p<0.1 (p=0.001) and would be continued with Regression Linier. From the test result showed correlation coefficients (r) in the amount of 0.411. Conclusion: There was a differences anxiety level between smoking students and non-smoking students of Faculty Letter and Fine Art Sebelas Maret University. Tobacco consumption had a moderate relationship with anxiety level. Heavier smoking on smoker student proved to be increasing anxiety level. Keywords: smoking student, non-smoking student, anxiety level